Investigating the use of selected Quranic and prophetic teaching methods (QPTMS) in teaching non-religious subjects in Islamic international schools in Malaysia - Eissa, Manar Abdullah (Kulliyah of Education, International Islamic University Malaysia, 2017)
The concept of Islamic education must be expanded to include the non-religious subjects in order to develop intellectually and morally competent individuals who will benefit their societies. Undoubtedly, in any education system, the teaching methods are among the important factors that influence the implementation of a curriculum according to the adopted philosophy. Teaching methods employed at schools in many countries, including the Islamic schools, tend to lean more towards practices based on Western theories. However, as Muslims, we have teaching guidelines mentioned in the Holy Quran and through the Sunnah of Prophet Muhammad, which seems to be ignored when teaching non-religious subjects. Hence, this research study attempts to assess the use of selected teaching methods derived from Quran and Sunnah in teaching non-religious subjects. This research categorizes the Quranic and Prophetic Teaching Methods (QPTMs) according to the recent major teaching and learning theories of Behaviorism, Cognitivism and ¬Constructivism. The selected Quranic and Prophetic Teaching Methods (QPTMs) are assessed based on their effectiveness in teaching, their ability to engage students in learning and their effect on developing the students' characters. Mixed-method research design was adopted in this study. The quantitative data were collected from 87 secondary school teachers who teach non-religious subjects in Islamic international schools located in Selangor, Malaysia. The teachers responded to a survey questionnaire developed by the researcher. The qualitative data was obtained from semi-structured one to one interviews with 6 selected teachers. The quantitative data were analyzed using descriptive statistics and chi-square technique. The findings of the study revealed that from the teachers' perspectives, the selected QPTMs are effective methods of teaching, and have positive effects when engaging students in learning. Moreover, the selected QPTMs can contribute to developing students' characters. However, the study revealed that the implementation of the selected QPTMs is restrained by several obstacles, such as the lack of professional training or teaching resources, the limited classroom time, and also the students' participation and behavior. Based on the findings, the study suggests enhancing the implementation of QPTMs in teaching non-religious subjects through providing effective professional training to the teachers in overcoming the existing obstacles.